1984
DOI: 10.1111/j.1365-2125.1984.tb02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone and levodopa in Parkinson's disease.

Abstract: To study the absorption of levodopa and interaction with the extracerebral dopamine antagonist domperidone, 15 patients with idiopathic Parkinson's disease were given levodopa 500 mg p.o., alone, and with domperidone pre-treatment. Domperidone pretreatment (10, 20, 40 mg, p.o., i.v. or i.m.) caused a mean 12% increase in peak plasma levodopa concentration, which occurred a mean of 10 min earlier than when levodopa was given alone. Parkinsonian disability scores were improved and peak clinical response occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Domperidone was not used in this study because it has been shown to slightly improve L-dopa absorption. 37 M pruriens grows widely throughout the tropics and is currently mostly planted to improve soil and provide animal feed, and to a smaller extent, for human consumption. It is believed the biological purpose of the L-dopa concentration is to protect the plant against insect attack.…”
Section: Discussionmentioning
confidence: 99%
“…Domperidone was not used in this study because it has been shown to slightly improve L-dopa absorption. 37 M pruriens grows widely throughout the tropics and is currently mostly planted to improve soil and provide animal feed, and to a smaller extent, for human consumption. It is believed the biological purpose of the L-dopa concentration is to protect the plant against insect attack.…”
Section: Discussionmentioning
confidence: 99%
“…Another successful approach to improve gastric symptoms with the peripheral dopamine antagonist domperidone had no significant effect on neurologic symptoms in Parkinson patients [51,53] possibly because the effect on levodopa kinetics was small [51]. Metoclopramide, a 5-HT 4 -agonist with peripheral and central dopamine antagonistic activity, also increases the bioavailability of levodopa [32] but because of its CNS actions it is suggested not to be given to patients with Parkinson's disease.…”
Section: ■ Combination With Prokineticsmentioning
confidence: 98%
“…[14,22] • Sensitzing effect of the heart for catecholamine [33] • α-methyldopa reduces levodopa response [21] • Pyridoxine (B6) increases the peripheral breakdown of levodopa and diminishes its efficacy [22,29,33] • Mequitazine decreases the L-dopa effect [29] • Metoclopramide and antacids increase levodopa resorption [21,29] • Domperidone slightly increases the bioavailability of levodopa [24] • Reduced therapeutic effect by reserpine, classical neuroleptics and opioids [14,22] Dopamine agonists • Ergot-agonists: increased effect of antihypertensive drugs [14,22] • Alpha-DHEC enhances the effect of platelet aggregation inhibitors • Lisuride increases the inclination to bleeding • Inhibition of particular enzymes of the P-450 system by bromocriptine and pergolide • Elevation of the macrolide antibiotic level (up to 4.6 times) by, e. g., cabergoline and bromocriptine • Caution when combining pramipexole with exclusively renally eliminated agents • High dose of Estrogens may increase the ropinirole level • Declining therapeutic effect by reserpine, classical neuroleptics and opioids [14,22] Selegiline • Contraindicated when used concurrently with SSRI (can trigger mania, shivering attacks, excessive sweating) and MAO inhibitors • Use cautiously in combination with TAD or COMT inhibitors (if selegiline > 10mg) • Do not combine with triptans -unpredictable interactions [33] and keep in mind the side effects seen with sibutramine [15] • Caution is required when used simultaneously with QT-interval prolonging agents (antiarrhythmic drugs, amantadine, domperidone) • Interaction with metoprolol (increased level) and several antibiotics • Reduced alcohol tolerance [22] Anticholinergics…”
Section: Parkinson's Disease and Gastroenterologymentioning
confidence: 99%